Manfaat Rehabilitasi Psikososial dalam Mendukung Pemulihan Orang dengan Gangguan Jiwa - Kartikasari, Ida Ayu; Hamid, Achir Yani S.; Hargiana, Giur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the benefits of psychosocial rehabilitation in supporting the recovery of people with mental disorders. The research method used was a literature review where article searches were carried out on the ProQuest, SpringerLink and EBSCOhost databases with publication years 2019-2023. The research results show that psychosocial rehabilitation has been proven to have a positive impact on the recovery of people with mental disorders. The positive impacts include: improving health behavior, improving functioning as an individual and increasing the ability to live independently and productively. Through psychosocial rehabilitation, people with mental disorders are able to increase their self-efficacy and satisfaction with their lives, which has a positive correlation in improving their quality of life. In conclusion, psychosocial rehabilitation is a program that must be integrated into the recovery of people with mental disorders. Keywords: People with Mental Disorders, Recovery, Psychosocial Rehabilitation